Analisis dan Perancangan Sistem Informasi Akuntansi Penjualan Jasa Desain - Cristian, Lianawati; Winarto, Winarto; Sonny, Sonny; Fernando, Edith (Bina Nusantara University, 2010)
The purpose of this paper is to analyze the problems that exist in CV TVB and design systems design services on credit sales for this company. The methodology used is the method of analysis and design methods. The method of analysis is the observation techniques, interviews, and book study, while the method is to use the object oriented design. Results to be achieved is in addition to this study is useful for companies in improving the effectiveness and efficiency in the sales cycle design services but also useful as a material for researchers refrensi others who want to investigate this and similar problems.Concluding, the sales system of computerized design services from order acceptance process to printing the reports can solve problems that occur in old systems and procedures.